MANAJEMEN OPERASI PENANGKAPAN GILLNET MILLENIUM DI DESA TABANIO KABUPATEN TANAH LAUT - Siti Aminah (Fish Scientiae, 2019)
Catching up with capture tool Gillnet Milinium is the most widely used of thebfishermen in the village of Tabanio. The arrest has a great business rivalries, wherebbusiness is not good management can affect the ability of the production units of thesebarrests and the impact on the income of fishermen. This research aims to know thebplanning unit's operating activities fishing with a gillnet Millennium and figure out thebimplementation of the operations of the unit catching fish with a gillnet Millenium Resultsbin can be shown that the planning activities unit arrest with gillnet millnenium dividedbthree of which is: (1) planning arrest operation gillnet,b(2 )planning burden work done thebhelmsman of a vessel and boat crews ( 3) planning of the season and regional gillnetbmillnenium arrest operation. and the implementation of the operations of the unit catchingbfish with a gillnet millennium divided three: (1) the Unit arrests in village Tabanio millnenium gillnet. (2) the method of operation of the capture tool in Tabanio the villageb(3) handling of catches in Tabanio the villag.